PENGARUH LATIHAN INTERVAL TRAINING TERHADAP DAYA TAHAN PADA TIM SEPAK BOLA SMK MUHAMMADIYAH 3 PEKANBARU - Riska, Indra; Slamet, Slamet; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research to determine the effect of interval training on endurance the football team in SMK Muhammadiyah 3 Pekanbaru.In this a researchers, the write took 14 students the total sample were 14 students which was taken from 14 students by using total sampling. The instrument used to collect data is a 2,4 km run test that ains to improve endurance capability.After that the data in though writer used statistic,based on the analysis of statical data,there are flat rate of pretest 11,60 and an average of postest 10,82,then the data normal is with an increase number of 0,78. The writer used normality test lilifors 0,05. The hypothesis proposed there is significant effect of interval training on endurance.. Based on analysis used t. test hitung 5,800 and t table 1,761. So 5,800 > 1,761. In ather words, there is significant effect of interval training on endurance the football team in SMK Muhammadiyah 3 Pekanbaru.Keywords : Interval Training, Endurance